The usefulness of endoscopic ultrasound-guided fine-needle aspiration for the diagnosis of pancreatic neuroendocrine tumors based on the World Health Organization classification. (November 2014) - Unno, Jun; Kanno, Atsushi; Masamune, Atsushi; Kasajima, Atsuko; Fujishima, Fumiyoshi; Ishida, Kazuyuki; Hamada, Shin; Kume, Kiyoshi; Kikuta, Kazuhiro; Hirota, Morihisa; Motoi, Fuyuhiko; Unno, Michiaki; et al.
Abstract Background. We assessed the controversial topic of using 22-gauge needles in endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) for the diagnosis and evaluation of Ki67 labeling indices (Ki67LI) of pancreatic neuroendocrine tumors (pNET). Methods. Thirty-eight patients with pNET who underwent EUS-FNA between January 1, 2008 and December 31, 2012 were enrolled in this study. When available, the Ki67LI and WHO classifications obtained by EUS-FNA and surgical resection were compared. Results. EUS-FNA with a 22-gauge needle acquired sufficient histological sample to correctly diagnose pNET in 35 cases (92.1%). Both EUS-FNA and surgical histological specimens were available for 19 cases, and grading classes of the 2 procedures were consistent in 17 cases (89.5%) according to the WHO classification based on the Ki67LI. Tumor size was associated with a difference in the Ki67LI between the 2 procedures, although the Ki67LI was almost completely consistent for tumors less than 18 mm in size. Conclusions. EUS-FNA with a 22-gauge needle is a safe and highly accurate technique for the diagnosis of pNET. There was a clear correlation between the Ki67LI of histological specimens acquired by EUS-FNA and surgery. EUS-FNA with a 22-gauge needle is useful to predict the WHO classification of pNET.